Bridging Tilawati: Elevating Al-Qur'an Reading Proficiency in Madrasah - Hidayah, Nurul; Fanani, Ahmad Aziz; Hidayah, Fathi; Mashuri, Imam; Baharun, Hasan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to analyze the effectiveness of the Tilawati method in improving Al-Qur'an reading skills at Madrasah Tsanawiyah Negeri (MTsN) 10 Banyuwangi. Using a qualitative approach with a case study design, this research involved the Madrasah Principal, Deputy Madrasah Principal, Al-Qur'an Teacher, and students as research subjects. Data collection techniques consist of observation, semi-structured interviews, and documentation, with data analysis carried out through data reduction, data presentation, and drawing according to the interactive model from Miles, Huberman, and Saldana. The research results show that the applying of the Tilawati method significantly improves students' Al-Qur'an reading skills through several indicators: systematization of recitation techniques, increased reading fluency, and in-depth understanding of the Al-Qur'an text. This method facilitates a supportive learning environment, promotes active interaction between students and teachers, and enriches students' learning experiences. This research concludes that the Tilawati method makes an important contribution to the teaching of the Qur'an in madrasas, with a positive impact on students' reading ability and understanding of recitation. It is hoped that these findings can become a reference for developing curricula and strategies for teaching the Koran in madrasas, as well as improving the overall quality of religious education.